SOSIALISASI TERAPI RELAKSASI BENSON TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Serly, Serly; Yumi Dian; Mohammad Candra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The high prevalence of hypertension in Indonesia, including at Bayu Asih Purwakarta Regional Hospital, demands effective treatment to prevent cardiovascular complications. Hypertension management does not only rely on pharmacological therapy, but also requires non-pharmacological interventions such as Benson relaxation therapy, which combines deep breathing techniques and repetition of words with spiritual meaning. This community service activity aims to improve the knowledge and skills of nurses at Karawang Regency Hospital in implementing Benson relaxation therapy. The activity implementation method uses a lecture and demonstration approach. The activity involved 20 participants, consisting of nurses and shift managers. Evaluation was carried out using a pre-test and post-test to assess knowledge improvements, as well as observation of skills during simulation practice. The results of the activity showed an increase in participant knowledge from an average score of 58% (pre-test) to 89% (post-test). In addition, 80% of participants were able to perform Benson relaxation therapy. Participants also showed high enthusiasm in participating in the entire series of activities. The socialization and training of Benson therapy have proven effective in improving the knowledge and skills of nurses at Karawang Regional Hospital